Biological aspects of feathers evolution: an integrative revision (Revista Brasileira Multidisciplinar, 2025)
The tretapod teguments has undergone several modifications throughout the their evolution, which it includes living and extinct groups, and it is related to several adaptive advantages, as the case of feather, a morphological trait that is currently restricted to birds. This character is the result of the tegument evolution in reptile groups since the Triassic. In this sense, this literature review aimed to investigate publications on the origin of feathers, their possible morphologies and ancestral stages, their development in living birds, the adaptive impacts of feathers and which groups presented feathers or their possible precursor stages. The ancestral feathers possibly arised in the Avemetatarsalia group whose origin refers to the Triassic period and would be structures that would enable thermal insulation and thus maintain higher metabolic rates than other groups in a competitive environment. Although there is no fossil evidence tracing morphological changes in feathers since their origin, an evolutionary model is accepted leading totake into account the evolutionary novelties that feathers present during their development in a characteristic scenario of Evo-Devo.
Keywords: evo-devo; tegumentar attachments; cell signalling pathways; Prum evolutionary model